Yeop Ali Pursuing DBA at 73 - New, Straits Times (New Straits Times, 2014)
I was aware that self-study pathway for the DBA programme would be a daunting task, but the attraction of being trained in applied research-based thinking and methods to define, implement and evaluate real business issues drove me to go for the challenge - Yeop Ali